2012
DOI: 10.1590/s0102-311x2012001100010
|View full text |Cite
|
Sign up to set email alerts
|

Assistência pré-natal nos serviços públicos e privados de saúde: estudo transversal de base populacional em Rio Grande, Rio Grande do Sul, Brasil

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
17
1
21

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 12 publications
6
17
1
21
Order By: Relevance
“…The proportion of records of tests found in this study was higher than or similar to other studies (1,7,8) , with a decline between the first consultation and the 30th week. This result is disturbing, as the tests provide information about the health status of pregnant women; they are also important in screening for diseases that could have negative consequences for mothers and fetuses, for example, sexually transmitted diseases such as syphilis, hepatitis B and AIDS, as well as anemia, gestational diabetes, maternal-fetal blood incompatibility, asymptomatic bacteriuria of pregnancy and toxoplasmosis.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The proportion of records of tests found in this study was higher than or similar to other studies (1,7,8) , with a decline between the first consultation and the 30th week. This result is disturbing, as the tests provide information about the health status of pregnant women; they are also important in screening for diseases that could have negative consequences for mothers and fetuses, for example, sexually transmitted diseases such as syphilis, hepatitis B and AIDS, as well as anemia, gestational diabetes, maternal-fetal blood incompatibility, asymptomatic bacteriuria of pregnancy and toxoplasmosis.…”
Section: Discussionsupporting
confidence: 71%
“…Also, there is a possibility of error in the execution of the tests, due to lack of specific materials, damaged equipment, delay in returning the results and loss of samples, among others. In a study conducted in the metropolitan region of São Paulo, among the hypotheses put forward to explain the low coverage of examinations in the third trimester, it is highlighted that professionals do not request the tests because they are out of the habit, and that some pregnant women fail to take tests even when they have been ordered (22) .The proportion of records of tests found in this study was higher than or similar to other studies (1,7,8) , with a decline between the first consultation and the 30th week. This result is disturbing, as the tests provide information about the health status of pregnant women; they are also important in screening for diseases that could have negative consequences for mothers and fetuses, for example, sexually transmitted diseases such as syphilis, hepatitis B and AIDS, as well as anemia, gestational diabetes, maternal-fetal blood incompatibility, asymptomatic bacteriuria of pregnancy and toxoplasmosis.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…Similar data were found in another study where most of the medical visits were in the public health network (17) . However, results of a study carried out in Rio Grande do Sul showed that pregnant women served by the public health system were disadvantaged in comparison with those served by the private health system that had better socio-economic, demographic, reproductive conditions, and coverage (18) . Regarding coverage of medical visits in the prenatal period, more than half of the women in this study received ≥7 medical checks.…”
Section: Discussionmentioning
confidence: 99%